Nanostructured Nickel/Ruthenium/Ruthenium‐Oxide Supercapacitor Displaying Exceptional High Frequency Response. (22nd November 2019) - Morag, Ahiud; Maman, Nitzan; Froumin, Natalya; Ezersky, Vladimir; Rechav, Katya; Jelinek, Raz
Abstract: The lower performance of pseudocapacitive supercapacitors in high‐frequency applications such as alternating current (AC) line filtering has been ascribed to presumed slow kinetics of redox processes compared to ion diffusion in electric double layer capacitors. A nickel‐deposited ruthenium/ruthenium‐oxide symmetric supercapacitor exhibiting remarkable electrochemical properties, particularly very high frequency response (>1 kHz) is developed. The electrodes are prepared via a simple process consisting of electrochemical reduction of ruthenium chloride on commercially available nickel foil as the current collector. A symmetric supercapacitor comprising nickel/ruthenium/ruthenium‐oxide electrodes and a polystyrene‐based thin spacer exhibits particularly fast scan rates, high power density of 1500 mW cm −2 (88 kW cm −3 ) with a maximum energy density of 0.58 µWh cm −2 (34 mWh cm −3 ), and excellent capacitance retention. Notably, supercapacitors prepared by the same synthetic method albeit using conventional gold substrate instead of nickel exhibit significantly lower frequency response. The exceptional electrochemical properties of the nickel/ruthenium/ruthenium‐oxide supercapacitor and simple electrode synthesis point to promising applicability in AC line filtering and power conditioning. In a broader context, this work demonstrates that, contrary to the widely held presumption, the kinetics of redox reactions at the active layers of pseudocapacitors may not be the primary barriers to high‐frequency applications. Abstract : A supercapacitor fabricated from electrodes comprising electrodeposited Ru/RuO2 on Ni foil exhibits exceptionally high capacitance at scan rates exceeding 1000 V s −1 . The electrode morphology, specifically the formation of Ru/RuO2 nanostructures upon the high surface area of the electrochemically etched nickel substrate, plays a critical role in accomplishing excellent electrochemical properties, particularly high frequency response (above 1 kHz).